An examination of prosody and second language sentence processing through pause insertion. (October 2021) - Fang, Lan; Xie, Yiyang; Yu, Keke; Wang, Ruiming; Schwieter, John W.
Objectives: Research on second language (L2) sentence comprehension often has examined reliance on semantic and syntactic information but has left aside for the most part the role of prosodic cues. In the present study, we compare less- and more-proficient L2 learners' integration of prosody and syntax structure during auditory L2 sentence comprehension. Design: Two group Chinese learners of L2 English learners (A2 and C1 levels) participated in an auditory comprehension task, which included sentences that had artificial pauses inserted either between or within syntactic boundaries. After hearing each sentence, learners were asked to judge the translation as 'identical' or 'not identical' on the keyboard. Data Analysis: We conducted t -tests and an analysis of variance to examine prosodic effects among the two learner groups. Findings: The results showed that both A2 and C1 learners were sensitive to pauses. However, the direction and magnitude of this sensitivity was significantly different for the two groups. A2 learners were faster to respond to auditory sentences in which a brief pause was placed within syntactic phrases. Contrarily, C1 learners responded faster when the brief pause was placed between syntactic phrases. Originality: Unique to the present study is the inclusion of the pause-insertion paradigm to examine the role of prosody in L2 auditory sentence processing. Implications: The results imply that the two groups of learners do not rely on prosodic and syntactic cues in the same manner when processing L2 sentences. We argue that the processing mechanisms involved in L2 sentence comprehension evolve hand-in-hand with L2 proficiency development. We discuss the implications of these findings for future research.